2020
DOI: 10.3390/vaccines8010029
|View full text |Cite
|
Sign up to set email alerts
|

Surface Immunogenic Protein of Streptococcus Group B is an Agonist of Toll-Like Receptors 2 and 4 and a Potential Immune Adjuvant

Abstract: Vaccine-induced protection against pathogens, especially subunit-based vaccines, are related to antigen properties but mainly in their ability to stimulate the immune system by the use of an adjuvant. Modern vaccines are formulated with a high level of antigen purity, where an efficient adjuvant is necessary. In this context, the use of protein Toll-Like Receptor (TLR) agonists as vaccine adjuvants has been highlighted because of their optimal immunogenicity and minimal toxicity. The Surface Immunogenic Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Given the in vivo and in vitro data obtained in this study, we propose that HylB may dampen proinflammatory cascades and microbicidal activity of first-line innate immune defenses such as neutrophils, thereby promoting bacterial replication and invasion of the amniotic cavity and fetus. We hypothesize that once bacteria have invaded the fetal niche, other proinflammatory, surface-associated bacterial factors (e.g., capsular polysaccharides [ 41 ], surface immunogenic protein [ 42 ], pilus [ 43 ]) overcome the immune-dampening effects of GBS HylB-digested HA fragments, triggering host PRRs and resulting in systemic fetal inflammation. A systemic fetal inflammatory response in GB37-infected fetuses may have triggered parturition in these animals, akin to fetal inflammatory response syndrome, which has been linked to preterm labor in humans ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the in vivo and in vitro data obtained in this study, we propose that HylB may dampen proinflammatory cascades and microbicidal activity of first-line innate immune defenses such as neutrophils, thereby promoting bacterial replication and invasion of the amniotic cavity and fetus. We hypothesize that once bacteria have invaded the fetal niche, other proinflammatory, surface-associated bacterial factors (e.g., capsular polysaccharides [ 41 ], surface immunogenic protein [ 42 ], pilus [ 43 ]) overcome the immune-dampening effects of GBS HylB-digested HA fragments, triggering host PRRs and resulting in systemic fetal inflammation. A systemic fetal inflammatory response in GB37-infected fetuses may have triggered parturition in these animals, akin to fetal inflammatory response syndrome, which has been linked to preterm labor in humans ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIP is considered a putative target for the development of a GBS vaccine because it is highly conserved among all GBS serotypes and induces a protective humoral and cellular immune response [13,19]. Moreover, rSIP is an agonist of toll-like receptor 2 (TLR2) and TLR4, which suggests a dual role in the generation of innate and adaptive immune responses against bacterial infection [15]. Previously, we demonstrated that an oral vaccination strategy composed of SIP plus alum adjuvant induces a reduction of GBS vaginal colonization, as well as opsonic antibodies [30].…”
Section: Discussionmentioning
confidence: 99%
“…Following the manufacturer’s instructions, we used the automated NucliSENS-EasyMAG platform (Biomerieux, Marcy l’Etoile, France) to purify total nucleic acids from 600,000 splenocytes contained in 500 μL of RPMI 1640 medium with 10% FBS, 25 mM β-mercaptoethanol, and penicillin/streptomycin. The splenocytes were obtained from the spleens of experimental mice and pulsed with SIP protein (purified by HPLC, as described by Diaz-Dinamarca et al [ 15 ]). The eluates were treated with DNase (Invitrogen, Carlsbad, CA, USA) to degrade the DNA in the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to hemocyanins, including the FLH used in this study, the recombinant surface immunogenic protein (rSIP) from Group B Streptococcus is a small protein. It was previously expressed in Escherichia coli and Pichia pastoris and had a molecular weight of 53 kDa with a β-folded structure and the ability to form dimers ( 27 ). This recombinant protein was analyzed as a vaccine against GBS in a preclinical trial.…”
Section: Introductionmentioning
confidence: 99%